Potentially inappropriate prescribing in elderly population: A study in medicine out-patient department - Sah, Ajit Kumar; Jha, Rajesh Kumar; Sah, Phoolgen; Basnet, Sangharshila (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Older individuals often suffer from multiple systemic diseases and are particularly more vulnerable to potentially inappropriate medicine prescribing. Inappropriate medication can cause serious medical problem for the elderly. The study was conducted with objectives to determine the prevalence of potentially inappropriate medicine (PIM) prescribing in older Nepalese patients in a medicine outpatient department. Materials & Methods: A prospective observational analysis of drugs prescribed in medicine out-patient department (OPD) of a tertiary hospital of central Nepal was conducted during November 2012 to October 2013 among 869 older adults aged 65 years and above. The use of potentially inappropriate medications (PIM) in elderly patients was analysed using Beer’s Criteria updated to 2013. Results: In the 869 patients included, the average number of drugs prescribed per prescription was 5.56. The most commonly used drugs were atenolol (24.3%), amlodipine (23.16%), paracetamol (17.6%), salbutamol (15.72%) and vitamin B complex (13.26%). The total number of medications prescribed was 4833. At least one instance of PIM was experienced by approximately 26.3% of patients when evaluated using the Beers criteria. Conclusion: Potentially inappropriate medications are highly prevalent among older patients attending medical OPD and are associated with number of medications prescribed. Further research is warranted to study the impact of PIMs towards health related outcomes in these elderly.